PENGARUH LEADERSHIP GAP SYNDROME TERHADAP MOTIVASI TENAGA KERJA MULTIGENERASI - Wijaya, Shierli (Publika Citra Media, 2024)
The telecommunications industry in Indonesia, dominated by Generations Y and Z, is confronted with a deficiency in leadership abilities, resulting in a leadership gap. The presence of many generations in the workforce leads to a variety of values and communication styles, which intensify conflict. This research investigates the impact of adaptive leadership, emotional intelligence, and managerial ability on the leadership gap syndrome within the multigenerational workforce of a telecommunications company in Indonesia. In a quantitative approach, data was collected from approximately 128 employees of PT XYZ. The study employs a convenience sampling method and utilizes SmartPLS version 4.0.9.6 for analysis. The findings revealed a significant negative relationship between adaptive leadership and the leadership gap syndrome, emphasizing the importance of leaders being adaptable. Emotional intelligence showed a weak or non-significant association with the syndrome, suggesting a nuanced relationship. Managerial ability demonstrated a negative association with the leadership gap syndrome, supporting the idea that competent managers can bridge leadership gaps. While the leadership gap syndrome did not directly impact multigenerational workforce motivation, leadership adaptability, emotional intelligence, and managerial ability positively influenced motivation through their effects on the syndrome.